Hemospray treatment is effective for lower gastrointestinal bleeding - Holster, I. Lisanne; Brullet, Enric; Kuipers, Ernst J.; Campo, Rafel; Fernández-Atutxa, Alberto; Tjwa, Eric T. T. L. (Endoscopy, 2014)
Acute lower gastrointestinal bleeding (LGIB) is diverse in origin and can be substantial, requiring urgent hemostasis. Hemospray is a promising novel hemostatic agent for upper gastrointestinal bleeding (UGIB). It has been claimed in a small series that the use of Hemospray is also feasible in LGIB. We aimed to expand our knowledge of the application of Hemospray for the treatment of LGIB in a wider range of conditions to further define the optimal patient population for this new therapeutic modality.We analyzed the outcomes of nine unselected consecutive patients with active LGIB treated with Hemospray in two major hospitals in Europe. Initial hemostasis was achieved after Hemospray application in all patients. Rebleeding occurred in two patients (22 %) who were on acetyl salicylic acid and presented with spurting bleeds. These preliminary data show that Hemospray can be effective in the management of LGIB, but suggest cautious use for patients on antithrombotic therapy and spurting bleeds.